Biblioteca digital virtual e a leitura de textos em tabletes - Monteagudo, Bárbara Cibelli da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present dissertation investigates the literary reader behaviour using tablet in virtual libraries of three students from the fourth year of the first cycle at a public state elementary school. The aim is also mapping the researcher's route in the use of the social supports reading at situations that it is given as language. The questions that guided this research looking for the possibility of using ebooks in schools are the followings: Is it possible for the school to appropriate the tablet usage to literary reading in school? What are the routes to be followed by the student and the teacher? The theoretical references of this research were authors such as Vygotski, Bakhtin, Foucambert, Arena and Bajard. The investigation's methodology was the research-action, using systematic observation records of the subjects-children, images and voice, and interview. The researcher exercised double role, as researcher and mediator. By investigating and mapping the paths taken by children in building their own virtual digital library, it was also observed the own way of organization of the researcher-mediator in the procedures for teaching the reading act. The data was produced, organized and analysed by thematic groups in an attempt of understanding the digital literary text reader's behaviour in virtual libraries, and the possibilities of use by children of e-books of children's literature in the classroom's everyday as social practices. The research results confirm the usefulness of tablet usage for the child organize a virtual digital library and perform the reading of digital works that lead to the construction of literary appreciation by students, as well as greater autonomy in search of texts. The otherness was also considered as playing an essential role in the construction of an environment which favours the expansion of culture and contributes, with the reading act, for the emancipation of students.

Esta dissertação investiga o comportamento de leitor literário com o uso do tablete em bibliotecas virtuais de três alunos do 4º ano do Ciclo I do Ensino Fundamental de uma escola pública da rede estadual. Pretende-se também mapear o percurso da pesquisadora no uso dos suportes sociais de leitura em situações que se constituem como linguagem. As questões que nortearam a pesquisa em busca da possibilidade do uso do e-book na escola são as seguintes: É possível à escola apropriar-se do uso do tablete para leitura literária na escola? Quais os percursos a serem trilhados pelo aluno e pelo professor? Os referenciais teóricos da pesquisa foram autores como Levy Vygotski, Mikhail Bakhtin, Jean Foucambert, Dagoberto Arena e Élie Bajard. A investigação teve como metodologia a pesquisa-ação, com uso de registros sistemáticos de observação dos sujeitos-crianças, por imagens e voz, e entrevista. A pesquisadora exerceu duplo papel, a de pesquisadora e mediadora. Ao investigar e mapear os caminhos percorridos pelas crianças na construção de sua própria biblioteca digital virtual observou-se também o próprio caminho da pesquisadora-mediadora na organização dos procedimentos para o ensino do ato de ler. Os dados foram produzidos, sistematizados e analisados por núcleos temáticos na tentativa de compreender o comportamento do leitor de texto literário digital nas bibliotecas virtuais, e as possibilidades de uso pelas crianças de e-books de literatura infantil no cotidiano da sala de aula como práticas sociais. Os resultados da pesquisa apontam ser possível o uso do tablete para a criança organizar uma biblioteca digital virtual e realizar a leitura de obras digitais que levem à construção da apreciação literária pelos alunos, bem como de maior autonomia na busca de textos. Consideramos também que a alteridade tem papel essencial na construção de um ambiente que favoreça a ampliação da cultura e contribua, com...
Keywords: Leitura (Ensino elementar); Literatura infantojuvenil; Educação de crianças; Crianças - Linguagem; Tablet; Children's literature